2018
DOI: 10.1007/s00018-018-2826-8
|View full text |Cite
|
Sign up to set email alerts
|

The impact of phosphatases on proliferative and survival signaling in cancer

Abstract: The dynamic and stringent coordination of kinase and phosphatase activity controls a myriad of physiologic processes. Aberrations that disrupt the balance of this interplay represent the basis of numerous diseases. For a variety of reasons, early work in this area portrayed kinases as the dominant actors in these signaling events with phosphatases playing a secondary role. In oncology, these efforts led to breakthroughs that have dramatically altered the course of certain diseases and directed vast resources t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 269 publications
1
25
0
Order By: Relevance
“…The PI3K/Akt pathway modulates many cellular processes, including proliferation, migration, and apoptosis, and the dysregulation of these signaling networks favors the growth and persistence of human cancer. 32 A flow cytometry assay demonstrated that the THSG proportion increased the cell population in early apoptosis in Q4, ADM, and the combination of both, which primarily distributed the cell population into late apoptosis in Q2, which was similar to the report that attributed this effect to the similarities in the excitation wavelength between PI and ADM autofluorescence. 33 This study further identifies the mechanism of the aforementioned apoptosis.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The PI3K/Akt pathway modulates many cellular processes, including proliferation, migration, and apoptosis, and the dysregulation of these signaling networks favors the growth and persistence of human cancer. 32 A flow cytometry assay demonstrated that the THSG proportion increased the cell population in early apoptosis in Q4, ADM, and the combination of both, which primarily distributed the cell population into late apoptosis in Q2, which was similar to the report that attributed this effect to the similarities in the excitation wavelength between PI and ADM autofluorescence. 33 This study further identifies the mechanism of the aforementioned apoptosis.…”
Section: Discussionsupporting
confidence: 77%
“…Akt kinase is phosphorylated by PI3K and controls cell apoptosis by regulating the antiapoptotic Bcl-2 protein. 32 Thus, we concluded that THSG and ADM individually may exert antitumor cellular proliferation effects via the inhibition of the VEGF/PI3K/Akt pathway and then induce apoptosis by affecting apoptosis-related proteins, as the two pathways are integrated. In addition, the combination treatment exhibited synergism in a similar manner ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 90%
“…Another potential reason is non-mutational plasticity induced by kinase inhibitors in GB cells (van den Heuvel et al, 2017). Notably, phosphorylation of GB driver pathways is not only regulated by kinases, but also by phosphatases (Narla et al, 2018;. Amongst them, Protein phosphatase 2A (PP2A) is a serine/threonine phosphatase that regulates multiple oncogenic kinase signaling pathways, as well as apoptotic mechanisms (Perrotti and Neviani, 2013;Kauko and Westermarck, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Activation of phosphoinositide 3‐kinase (PI3K)/AKT tyrosine kinase cascade (also known as AKT or PKB pathway) contributes to anti‐apoptosis and cell survival in various cancers (Narlaet al, 2018). Increased AKT activity accounts for acquired resistance to antitumor agents (Cassinelli et al, 2013).…”
Section: Introductionmentioning
confidence: 99%